The making of an Identity: the Phoenician communities of the Iberian Peninsula and their integration in the Roman world - Machuca Prieto, Francisco (My University, 2018)
This presentation aims to report the conclusions of our dissertation, titled The Phoenician communities of the Iberian Peninsula and their integration in the Roman world: an identity perspective . The period under discussion extends from the end of the Second Punic War in 206 BCE to the Flavian era. Above all, the paper focuses on the cultural and ethnic dimensions of the process of inte gration of communities of Phoenician origin and tradition in the southern part of the Iberian Peninsula into the structures of Roman Empire. Our investigation has as its primary goal the explanation of the mechanisms of construction of collective identity and forms of expression which have come about in the midst of these communities along the road to becoming established as Roman ciuitates . This dissertation also attempts to improve upon the one - dimensional classical perspectives concerning the poorly - nam ed process of «Romanization». This in turn leads us to reinterpret the known «Phoenician» cultural «persistences» as a reflection of the possible existence of ethnic workings and re - workings by means of falsely or actually ancient components with the goal of legitimation within the dynamic Roman world.
Keywords: Fenicios - Península ibérica; Globalisation; Identity; Hispania; Phoenicians